Skilled Labor Mobility and Migration - Elisabetta Gentile (Edward Elgar Publishing, 2019)
One of the primary objectives of the ASEAN Economic Community (AEC), established in 2015, was to boost skilled labor mobility within the region. This insightful book takes stock of the existing trends and patterns of skilled labor migration in the ASEAN. It endeavors to identify the likely winners and losers from the free movement of natural persons within the region through counterfactual policy simulations. Finally, it discusses existing issues and obstacles through case studies, as well as other sectoral examples.